Patient care and customer services during the COVID-19 pandemic at accredited pharmacies: Pharmacists and patients' perspectives - Chamipa Phanudulkitti; Surangkana Puengrung; Karen Bell Farris (Exploratory Research in Clinical and Social Pharmacy, 2023)
Background: Community pharmacists are now the most accessible healthcare professionals, providing advice, information, drugs, and devices across the globe during the COVID-19 pandemic. In Thailand, accredited community pharmacies meet higher standards than qualified community pharmacies, but little is known about the perspectives of accredited community pharmacists and patients in this emergency situation. This study aimed to assess pharmacists' and patients' perspectives on the challenges and opportunities they faced in providing or receiving patient care and services during the COVID-19 pandemic. Methods: A cross-sectional study was conducted in March–August 2022 in a province located in the eastern part of Thailand. Participants of the study were full-time pharmacists and patients at accredited community pharmacies. A convergent mixed methods design was used and involved quantitative data about the perspectives of participants measured by online self-administered surveys and qualitative open-ended questions. Results: Twenty pharmacists and 416 patients provided complete responses. The meta-inferences were expansive in three standards including physical evidence, quality management, and good pharmacy practices/services for both groups of participants. For the social/community involvement standard, pharmacists' and patients' opinions (free-text responses) confirmed their perspective scores. Conclusions: This study highlights community pharmacy's crucial role in maintaining essential healthcare services during the pandemic, with patients acknowledging and appreciating the dedication of community pharmacists. The mixed methods findings provide valuable insights into pharmacists' and patients' perspectives, facilitating a deeper understanding and exploration of the potential roles community pharmacists can play in a post-pandemic world, embracing new technologies for improved systems.